2021
DOI: 10.4103/ua.ua_130_20
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric urology surgical practice in the time of COVID-19

Abstract: Purpose: Our study aimed to evaluate the effect of COVID-19 on pediatric urology practice in the Kingdom of Saudi Arabia (KSA). Methods: Data of 10 tertiary hospitals in KSA were retrospectively analyzed. Data of outpatient department (OPD) visits and pediatric urology surgical procedures from January 1, 2019, to April 30, 2019, and from January 1, 2020, to April 30, 2020, were extracted. The primary outcome was to compare OPD visits and pediatric urology workload in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Since the COVID-19 infection and global spread, social distancing and reduced travel have been strictly advised to control the disease spreading ( 8 ). Usage of medical resources has also been affected, primarily by increased critically ill patients and overcrowding of medical facilities ( 9 ). Reduced hospital visits and delays in hospitalization and operations for pediatric patients have been reported due to the parents' hesitancy for symptoms not related to COVID-19, which may lead to more complications and poor outcomes ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the COVID-19 infection and global spread, social distancing and reduced travel have been strictly advised to control the disease spreading ( 8 ). Usage of medical resources has also been affected, primarily by increased critically ill patients and overcrowding of medical facilities ( 9 ). Reduced hospital visits and delays in hospitalization and operations for pediatric patients have been reported due to the parents' hesitancy for symptoms not related to COVID-19, which may lead to more complications and poor outcomes ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Egypt recorded the highest rates (65.1%), followed by the UAE (58.2%) and the KSA (45.2%) in terms of high-priority surgeries such as kidney stone obstruction and cancer operations, including TURBT and radical nephrectomy. In line with these findings, Raheem et al [ 23 ] indicated that urology elective treatments in the KSA declined by 34.3% in the first three months of 2020 compared to the same period in 2019, along with prioritizing emergency interventions to prevent permanent disease development or organ destruction, such as urolithiasis-related procedures.…”
Section: Discussionmentioning
confidence: 93%